Ethnobotany, phytochemistry, and biological activities of Psidium guajava in the treatment of diarrhea: a review - Liu, Chengmei; Jullian, Valérie; Chassagne, François (Frontiers in Pharmacology, 2024)
Psidium guajava is a tropical tree that is widely used in traditional medicine, especially for treating diarrhea. While P. guajava has been the subject of numerous reviews, none have specifically examined its ethnobotany, pharmacology, and phytochemistry in relation to its antidiarrheal activity. This review aims to summarize the evidence of effectiveness and safety of P. guajava in the treatment of diarrhea. Literature searches were conducted through Web of Science, PubMed, and ScienceDirect by using keywords "Psidium guajava" and "diarrhea" in October 2022. A total of 189 studies were included in this review. P. guajava is widely used in traditional medicine in 44 countries. Decoction and oral were the most represented method of preparation and administration, respectively, while leaves represented the most frequently cited part of the plant. Around 27 antidiarrheal or antibacterial compounds have been isolated and identified, including benzophenone glycosides, terpenes, polysaccharides, phenols, and flavonoids. This article presents ethnobotanical and pharmacological evidence for the efficacy of P. guajava leaves in the treatment of diarrhea and provides reference information for further investigation of this plant. However, despite the large number of publications on the topic, there are still some questions to answer: are quercetin and its glycosides the only ones to act as antidiarrheal agents? What is the mechanism of action of P. guajava antidiarrheal compounds? Are the use of guava leaves safe in all types of populations including children, and at what dosage? To answer these questions, more complete phytochemical studies and systematic clinical trials are needed.